Suitability of potato variety Kufri Surya for early planting under warmer condition in the Sone riverbed of Patna district in Bihar - singh, siddhartha kumar (Potato Journal, 2016)
A field trial was conducted during winter season of 2011-12 and 2012-13 at farmer’s fields in participatory mode with three treatments to assess the suitability of potato variety Kufri Surya for early planting under warmer condition in the Sone riverbed of Patna district in Bihar. Plant emergence was not influenced by the treatments however Kufri Surya recorded significantly taller plants, more number of leaves per plant and consequently greater LAI, significantly higher total aggregate and marketable tuber yield and tuber number as compared to Lal Gulab at farmer’s management level. The highest total (25.51 t/ha) and marketable (23.05 t/ha ) tuber yield and aggregate tuber population was recorded in Kufri Surya with recommended package of practices. Highest gross return (Rs.1,73,379/ha) as well as net return (Rs 1,00,714/ha) and uptake of N (100 Kg/ ha), P (10.4 Kg/ha) and K (114.8 Kg/ ha) were obtained with the cultivation of Kufri Surya at improved management practices as recommended by CPRI. Thus Kufri Surya can be economically recommended for cultivation under early planting condition in Sone river bed area of Patna district of Bihar for higher yield and economic return.